To study the existing system of surgical safety for cataract surgery at tertiary care ophthalmic centre to implement WHO surgical safety checklist - Garg, Ruchi; Garg, Neeraj; Gupta, Shakti Kumar; Titiyal, J. S.; Mahesh, R. (International Journal of Research in Medical Sciences, 2017)
Background: Dr. Rajendra Prasad Centre for Ophthalmic Sciences, named after the first President of India, was established on the 10th of March, 1967 as a National centre for ophthalmic science, to provide state of the art patient care, expand human resources for medical education and undertake research to find solutions to eye health problems of national importance. Average numbers of cataract surgeries performed per month are 700 to 1000. Methods: Anticipating implementation in 50% cases hundred cases of cataract surgery were observed to study the existing system of surgical safety followed at Dr. R.P. Center and gap analysis done, against the WHO surgical safety checklist for cataract surgery. Modified WHO surgical safety checklist for cataract surgery was developed and implemented in the centre. Barriers in implementation of surgical safety checklist were also identified, and remedial measures suggested. Results: Significant improvement was noticed in all the parameters after introduction of modified checklist. The additional points which were added in modified surgical safety checklist were implemented in almost all the cases by the nursing staff. Overall mean compliance percentage before implementation of modified surgical safety check list at Dr. R.P.C was 37%±10.1 (P=0.001). While after introduction of modified surgical safety check list the mean compliance has improved to 62.7%±10.3, Wilcoxon rank sum test/Independent test is applied for each domain. Conclusions: Cataract procedure is the most common surgical procedure performed in the population in India. High volume and high turnover increase the potential for errors. Compliance to surgical safety check list before intervention was 32%. After intervention in form of a focus group discussion and introduction of modified surgical safety check list has resulted in increase in the compliance rate to 67%. This study revealed that changes or additional work is not happily accepted by the staff. After six months of intervention of modified surgical safety checklist compliance rate was still high, this suggests that constant supervision and monitoring by senior staff can sustain the compliance rate.